Analysis of Air Pollution Level In Settlement Area Using Passive Sampler Method - Normalia Djamal; Andi Suryanto; Andi Artiningsih; Nizar Nasrullah; Rosyi Damayanti T Manningtyas; Yessy Velina (International Journal of Hydrological and Environmental for Sustainability, 2022)
Air pollution, especially in big cities in Indonesia, has reached a very worrying level. The main sources of air pollution come from various human activities, including industry, transportation, offices, and housing. These various activities are the biggest contribution of air pollutants that are released into the free air. In this study, observations and measurements of air pollution levels were carried out in the Final Disposal Site (FDS). The absence of good waste management in Sinjai Regency has triggered the community to manage waste by means of Open Dumping, where waste is simply dumped in a landfill without any treatment. Pollutant gas originating from the landfill will produce harmful gases, including Nitrogen Dioxide (NO2), Sulfur Dioxide (SO2) and others. This study aims to determine the concentrations of Nitrogen Dioxide (NO2) and Sulfur Dioxide (SO2) in Final Disposal Site (FDS) Tondong and in residential areas around Tondong FDS, Sinjai Regency by using the passive sampler method. The test results obtained are the NO2 value at point 1 which is 3.69 g/m3, point 2 is 5.25 g/m3, point 3 is 3.1 g/m3 and point 4 is 7.1 g/m3 with an average value The average NO2 parameter test is 4.785 g/m3. While the SO2 value at point 1 is 4.46 g/m3, point 2 is 7.34 g/m3, point 3 is 8.47 g/m3 and point 4 is 5.93 g/m3. The average value of the SO2 parameter test is 6.55 g/m3. Calculating the Air Quality Index based on the Regulation of the Minister of Environment and Forestry of the Republic of Indonesia Number 27 of 2021 concerning the Environmental Quality Index, air pollution at the Tondong Landfill is worth 93.14 indicating the very good category.